Teaching Ophthalmology Residents Clinical Optics Via a Flipped Classroom Curriculum - Tu, Daniel C.; Park, Dong-Wouk; Krisciunas, Tammie; Hwang, Thomas S. (Journal of Academic Ophthalmology, 2019)
Background Clinical optics is an essential part of ophthalmology resident education that can be challenging for both learners and teachers when taught using a lecture format. The effectiveness of a flipped classroom approach in this context has not been formally evaluated.Objective The main purpose of this article is to compare the effectiveness of flipped classroom versus lecture-based clinical optics curricula in a graduate medical education setting.Design Retrospective, nonrandomized, pre- and post-interventional study from 2009 to 2016.Setting, Participants Ophthalmology residency program at the Casey Eye Institute, Oregon Health & Science University, an academic medical center in the United States. Participants included all ophthalmology residents able to take at least one Ophthalmic Knowledge Assessment Program (OKAP) examination during the years 2009 to 2016.Methods The clinical optics curriculum was changed from a lecture-based series to a flipped classroom curriculum and moved from the fall to winter during the 2012 to 2013 academic year. No major changes were made to the curriculum in other subject areas during the study period. Resident performance on the OKAP annual national in-service examination for the 4 years before and after the optics curriculum change was compared. Specifically, the scaled subtest scores from the Optics, Refraction, and Contact Lens subsection were examined, while scores from the 10 nonoptics subsections served as controls.Results Scores from 57 resident test administrations before the optics curriculum change and 59 after the optic curriculum change were available for comparison. The Optics, Refraction, and Contact Lens subsection mean scores were 50.37 ± 2.31 and 57.27 ± 2.47 before and after the optics curriculum change, respectively (mean ± 95% confidence interval). This was the only subsection score to show a statistically significant difference after the optics curriculum change (p = 0.00008).Conclusions and Relevance In comparison to a lecture-based curriculum, a flipped classroom approach to clinical optics education was found to be associated with higher ophthalmology resident performance on the optics subsection of the OKAP examination. Our study suggests that a flipped classroom format may be more effective than traditional lectures for teaching clinical optics in a graduate medical education setting.
Keywords: optics; flipped classroom; problem-based learning; ophthalmology; residency; medical education